Caring for people with dementia during the COVID-19 pandemic:a systematic review - Juan Jesús Robles-García; José Ángel Martínez-López (Dementia & Neuropsychologia)
ABSTRACT Human history has been linked to numerous risks to survival, with pandemics being a constant in human life. People suffering from dementia experienced greater difficulties accessing healthcare and treatment during the COVID-19 pandemic. Objective: To identify how the COVID-19 pandemic influenced care for people with dementia or cognitive impairment. Methods: This research work is a systematic review conducted with a literature search in four databases such as Web of Science, Scopus, EBSCOHost, Cochrane Library, and ProQuest, following the methodological proposals of the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guide. Results: The bibliographic research in the different databases offered a total of 561 records, of which 23 were chosen to elaborate the results. The main results were the increasing cognitive impairment and psychosocial consequences of social distancing during the pandemic, including sadness, helplessness, and abandonment in patients or feelings of burnout and overload in caregivers and health professionals. Conclusion: The COVID-19 placed patients with dementia in the background. During the pandemic, attention was focused primarily on emergencies and not so much on the monitoring of chronic diseases, which also caused psycho-emotional and social worsening.